2005
DOI: 10.1007/s00464-005-0171-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of strangulated hernias

Abstract: For selected patients, the TAPP approach appears to be a good therapeutic option for strangulated hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 14 publications
1
38
1
4
Order By: Relevance
“…Selected series, including patients with and without bowel resection, published by groups experienced in laparoscopic repair, report low complication rate and mortality [23][24][25]. These encouraging results have been obtained in a limited number of patients [24] and with a significant proportion of them being excluded due to comorbidities [23,25].…”
Section: Discussionmentioning
confidence: 83%
“…Selected series, including patients with and without bowel resection, published by groups experienced in laparoscopic repair, report low complication rate and mortality [23][24][25]. These encouraging results have been obtained in a limited number of patients [24] and with a significant proportion of them being excluded due to comorbidities [23,25].…”
Section: Discussionmentioning
confidence: 83%
“…Besides the perishing pathological conditions and possible organ injuries, the extensive adhesiolysis, remnant of hernia sac and the need for mesh fixation with tacks that may be a cause for seroma should also be taken into consideration. Up to now, laparoscopic transabdominal preperitoneal approach (TAPP) is the preferred method to deal with incarcerated hernia by most surgeons [18][19][20][21][22]. Ferzli GS et al [23] have used a combined technique to scrotal hernia.…”
Section: Discussionmentioning
confidence: 98%
“…A recent meta-analysis on the risk factors for meshrelated infections after hernia repair surgery estimated the crude mesh infection rate to be 5 % [26]. The reported incidence of mesh infection in 16 studies reporting on the use of prosthetic mesh repair in the emergency management of the acutely incarcerated and/or strangulated ventral and groin hernias is 0.2 % despite the fact that resectionanastomosis of non-viable bowel was performed in 14.7 % of the patients (Table 5) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In the present study, none of the 18 patients who had resection-anastomosis of nonviable small intestine developed mesh infection, and this complication was encountered in one patient (1.25 %) whose hernia contained viable contents.…”
Section: -72mentioning
confidence: 99%
“…Such policy leaves patients with complicated hernias, that is, acute incarceration and/or strangulation at an unacceptably high risk of recurrence. Although several studies have clearly demonstrated the safety and efficacy of prosthetic mesh repair in the emergency management of the acutely incarcerated and/or strangulated inguinal and ventral hernias, however, surgeons remained both skeptical and reluctant to use prosthetics in such settings [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%